The Relation of Work Environment and Stress in Classroom Management among Preschool Teachers - Ambotang, Abdul Said; Mohd Hashim, Muhamad Hisyam (Journal of Techno-Social, 2010)
The purpose of this research is to observe how far preschool teachers endure stress in carrying out their job which is influenced by the work climate including the management of classroom. This research is carried out by choosing a group of 55 preschool teachers as respondents in the district of Keningau Sabah. Data is analyzed using descriptive method (mean), inferential (T-test) Statistic, one way ANOVA and Pearson correlation. Result showed that there were high positive relationships between the work climate with stress level among the teachers. (r = 0.807, p<0.01) and classroom management with level of stress (r = 0.770, p< 0.01). It is hoped that with the information obtained by this research will assist the Malaysian Ministry of Education in planning and designing a suitable programme to overcome the stress problem faced by teachers especially preschool teachers towards improving the teaching profession quality in the near future.